Physiological Approach to the Use of the Natural Compound Quinate in the Control of Sensitive and Resistant Papaver rhoeas - Ana Zabalza; Ainhoa Zulet-González; Maria Barco-Antoñanzas; Mikel V. Eceiza; Miriam Gil-Monreal; Mercedes Royuela (Plants, 2020)
Quinate (1,3,4,5-tetrahydroxycyclohexanecarboxylate) is a compound synthesized in plants through a side-branch of the shikimate biosynthesis pathway, which is accumulated after glyphosate and acetolactate synthase inhibiting herbicides (ALS-inhibitors) and has phytotoxic potential. The objective of this study was to evaluate the phytotoxicity of quinate on several weed species. Among the species evaluated, Cynodon dactylon, Bromus diandrus, Lolium rigidum, Sinapis alba, and Papaver rhoeas, P. rhoeas was the most sensitive, and its growth was controlled with quinate concentrations above 100 mM at the phenological stage of 6–8 true leaves. A physiological study, including the shikimate pathway and the physiological markers of ALS-inhibitors (carbohydrates and amino acids), was performed in the sensitive and resistant plants treated with sulfonylureas or quinate. The typical physiological effects of ALS-inhibitors were detected in the sensitive population (free amino acid and carbohydrate accumulation) and not detected in the resistant population. The mode of action of quinate appeared to be related to general perturbations in their carbon/nitrogen metabolism rather than to specific changes in the shikimate pathway. These results suggest the possibility of using quinate in the weed control management of P. rhoeas.